THE INFLUENCE OF PRUDENCE AND PROFITABILITY ON PROFIT QUALITY WITH COMPANY SIZE AS AN INTERVENING VARIABLE - Nelcie Valensya Mussa; Agus Munandar (SEAN Institute, 2023)
This study aims to determine the effect of prudence, profitability on earnings quality with company size as an intervening variable. In this study the independent variables are prudence and profitability, the dependent variables are earnings quality and company size as intervening variables. This research was conducted using a quantitative explanatory method using secondary data. The population in this study are all food and beverage companies on the Indonesian stock exchange, totaling 39 companies taking 2 years of research starting from 2020-2021. The sampling method uses a purposive sampling method to get a suitable representative so that there are 60 financial statements used as data in this study. The results showed that prudence has a positive effect on earnings quality, profitability does not affect earnings quality, company size does not affect earnings quality, prudence has no effect on firm size, profitability affects firm size, and firm size cannot mediate the relationship between prudence and profitability on earnings quality.